Cochrane corner: Extracts from The Cochrane Library: tonsillectomy or adenotonsillectomy versus non-surgical management for obstructive sleep-disordered breathing in children - Burton, M; Goldstein, N; Rosenfeld, R (Sage Publications, 2016)
The “Cochrane Corner” is a section in the journal that highlights systematic reviews relevant to otolaryngology–head and neck surgery, with invited commentary to aid clinical decision making. This installment features a Cochrane Review on tonsillectomy for obstructive sleep-disordered breathing (oSDB) in children, which finds moderate-quality evidence that surgery improves symptoms, behavior, and quality of life compared to nonsurgical management. The results apply to nonsyndromic children with SDB confirmed by polysomnography and must be balanced against a favorable natural history in many cases.